Elevation, climate, and soil characteristics influence Juniperus procera dieback and restoration efforts in Southwestern Saudi Arabia - Hatim M. Al-Yasi (Scientific Reports)
Abstract Dieback episodes in Juniperus procera, driven by climate and soil characteristics, are documented across forest ecosystems worldwide. However, these phenomena remain underexplored in Saudi Arabia, especially concerning elevation gradients. We conducted an analysis of the environmental characteristics that led to dieback events impacting the Juniperus procera scrublands in the southwestern mountainous region. This study was carried out across three sites in Saudi Arabia: Taif (L1–L4), Al-Baha (L5–L7), and Aseer (L8–L12). Our approach included efforts toward biological restoration by applying NPK fertilizer at concentrations of 10 and 15 g/L to the threatened J. procera trees. The data revealed that the peak concentrations of nitrogen, potassium, phosphorus, calcium, and organic matter, alongside the lowest pH value, were observed at an elevation of 3238 m (L10) in the Aseer region. In contrast, the minimum levels of nitrogen, potassium, phosphorus, calcium, and organic matter, alongside the highest pH value, were observed at an elevation of 2672 m in L1 of the Taif region. Interestingly, Juniper populations presented the most favorable health status, with a dieback rate of only 5% at an elevation of 2966 m in the Taif region. In contrast, the most significant dieback, reaching 72%, was observed at an elevation of 2780 m in the same region. A notable negative correlation was identified between juniper dieback and elevation, as well as between soil variables, including N, K+, Na+, P, Ca+ 2, and OM (r = −0.48, −0.63, −0.46, −0.48, −0.63, −0.41, and −0.48, respectively). Furthermore, notable relationships were identified between elevated terrains and the concentrations of nitrogen (N), potassium (K+), sodium (Na+), phosphorus (P), and calcium (Ca+ 2) and magnesium (Mg+ 2) in the soil, alongside a significant association with the pH. Thus, this research revealed that variations in climate and soil adversely affect juniper dieback.